Desmoids and Genotype in Familial Adenomatous Polyposis. Issue 4 (April 2015) - Church, James; Xhaja, Xhileta; LaGuardia, Lisa; O'Malley, Margaret; Burke, Carol; Kalady, Matthew
Abstract : BACKGROUND: Desmoid disease can be a serious, life-threatening complication of familial adenomatous polyposis. The ability to predict patients at increased desmoid risk is important, but a convincing genotype-phenotype correlation for desmoid formation has not yet been described. PURPOSE: The aim of this study is to assess the relationship between desmoid disease and genotype in patients with familial adenomatous polyposis. DESIGN: This is a cohort study. PATIENTS: All patients with familial adenomatous polyposis and a documented pathogenic APC mutation in themselves or a first-degree relative were selected. MAIN OUTCOMES MEASURES: The comparison of genotype and the presence, stage, and site of desmoid disease are the primary end points of this study. RESULTS: Three hundred twenty-three patients from 219 families were identified. Mutations spanned the length of the gene, from codon 213 to codon 2051. Desmoid disease was diagnosed in 77 patients from 68 families. Desmoid disease was found in 14.9% of patients with a mutation 5′ of codon 400, 23.2% of patients with a mutation from codon 401 to 1400, and in 37.1% of those with a mutation 3′ of 1400. All patients with 5′ mutations had stage I or II abdominal desmoid disease, and all tumors were stable or shrinking. Twelve percent of patients who had desmoid disease with mutations between codons 400 and 1400 had stage III or IV desmoid disease, and 5 of 42 (12%) tumors were growing at the time of the study. There had been 2 desmoid-related deaths. Almost half (44%) of patients who had desmoid disease with mutations 3′ of codon 1400 had stage III or IV disease. Three of 14 tumors were growing (21%), and there were 4 desmoid-related deaths. LIMITATIONS: This study was conducted at a tertiary referral center, and there was no systematic surveillance for desmoids. CONCLUSION: Desmoid disease occurs in patients who have familial adenomatous polyposis with almost any APC mutation, although there is an increased propensity in those with a 3′ mutation. The incidence and severity of the desmoid disease are related to the site of the mutation.